The Projected Economic Burden of Non-Communicable Diseases Attributable to Overweight in Brazil by 2030 - De Moraes-Ferrari, G (Elsevier B.V., 2024)
Objectives: The prevalence of overweight increases the risk of several non-communicable diseases (NCDs) and, consequently, the costs of health care systems. In this study, we aimed to project the economic burden of NCDs attributable to overweight in Brazil between 2021 and 2030. Methods: A cohort simulation of adults (17–117 years) using multistate lifetable modeling was used to estimate the costs of NCDs attributable to overweight in Brazil. The projections of direct health care costs (outpatient and inpatient expenses in the Unified Health System) and indirect costs (years of productive life lost) considered different trajectories of the prevalence of overweight between 2021 and 2030. Results: In 2019, the prevalence of overweight was 55.4% in the adult Brazilian population. We estimate that around 1.8 billion international dollars (Int$) would be spent on the direct health care cost of NCDs between 2021 and 2030, through the continued increase in overweight prevalence observed between 2006 and 2020. The indirect costs over the same time would be approximately 20.1 billion Int$. We estimate that halving the annual increase in body mass index slope from the beginning of 2021 until 2030 would save 20.2 million Int$ direct and indirect costs by 2030. In the scenario of keeping the prevalence of overweight observed in 2019 constant until 2030, the savings would be 40.8 million Int$. Finally, in the scenario of a 6.7% reduction in the prevalence of overweight observed in 2019 (to be achieved gradually until 2030), 74.1 million Int$ would be saved. Conclusions: These results highlight the high economic burden of overweight in the Brazilian adult population. © 2024 The Royal Society for Public Health